Strategic Agility and Sustainable Competitive Advantage: How to Leverage Top Management Team Characteristics - Karoney, Farida; Awino , Zachary; Aosa, Evans; Wainaina, Gituro (European Journal of Business and Strategic Management, 2024)
Purpose: Ubiquitous disruptive innovations and technologies, frequently changing consumer behaviour, and evolving market dynamics in Kenya, have compelled television stations to constantly explore innovative ways to achieve long term business sustainability. Firms must be ambidextrous; balancing the tensions of excelling in current businesses while exploring opportunities for future growth. This requires top leadership teams that are well suited to the challenge of steering organisations in disrupted business contexts. This paper investigated the effect of top management team characteristics on the linkage of strategic agility and sustainable competitive advantage of licensed television stations in Kenya. Methodology: A descriptive cross-sectional survey was employed and primary data was collected using a semi-structured questionnaire. Data from 210 licensed television stations that were operational at the time of the study was analysed using structural equation modelling (SEM). Findings: The results of the study indicated that strategic agility had a positive and significant effect on sustainable competitive advantage of licensed television stations in Kenya. Further, top management team characteristics were a mediator on the nexus between strategic agility and sustainable competitive advantage, as well as a predictor variable of sustainable competitive advantage of licensed television firms in Kenya. Unique Contribution to Theory, Practice and Policy: The research was underpinned by the dynamic capabilities, resource-based view and upper echelons theories. The implication is that, to achieve sustainable competitive advantage, it is crucial for the top management team to possess specific attributes, including a balanced mix of both young and experienced members, diversity in functional backgrounds (especially those with knowledge of disruptive technologies and innovations), varying educational levels, and a mix of long-tenured and new managers.